2021
DOI: 10.2106/jbjs.oa.21.00045
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Anterior and Posterior Tilt of Garden I-II Femoral Neck Fractures Predict Treatment Failure and Need for Reoperation in Patients Over 60 Years

Abstract: Background:The purpose of the present study was to estimate the effect of preoperative fracture tilt and to scrutinize the effect of anterior tilt on the risk of treatment failure in patients with Garden Type-I and II femoral neck fractures that are treated with internal fixation.Methods:A retrospective multicenter study was performed on a consecutive series of patients ≥60 years of age who had undergone primary internal fixation for the treatment of Garden Type-I and II femoral neck fractures. The study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Difficulty obtaining perfect lateral radiographs to measure the PTA because of soft-tissue envelope or other possibilities should be considered. Although a high intraobserver and interobserver reliability is reported in measuring the PTA on radiographs, 8,10,18,21,25,26,28 this is a potential source of bias. We believe it would be reasonable to obtain a CT should the concern of accurately measuring the PTA on a lateral radiograph arise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Difficulty obtaining perfect lateral radiographs to measure the PTA because of soft-tissue envelope or other possibilities should be considered. Although a high intraobserver and interobserver reliability is reported in measuring the PTA on radiographs, 8,10,18,21,25,26,28 this is a potential source of bias. We believe it would be reasonable to obtain a CT should the concern of accurately measuring the PTA on a lateral radiograph arise.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated high interobserver and intraobserver reliability of the PTA measurement method described by Palm et al, which relies on appreciating the cortical lines of the femoral head and neck. 8,10,18,21,25,26,28 If adequate lateral radiographs to measure the posterior tilt are difficult to obtain, augmenting the workup with a CT scan and assessing axial cuts has been shown to be an effective alternative. 21 This was defined as the "retroversion angle" by Shin et al, 21 which provides a similar assessment to PTA seen on lateral radiographs, demonstrating a 0.961 interobserver correlation coefficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preoperative and precise assessment of the posterior tilt is optimal for the surgeon to determine the need for optimal reduction. Taking into account that this subtype of Garden type I and II with posterior tilt greater than 20° behaves like an unstable fracture, causing avascular necrosis due to vascular kinking and tearing, an exact preoperative assessment, especially in elderly patients, may elicit primary arthroplasty [ 24 , 25 ]. However, because usually applied measurement techniques do not fit for areas proximal to the intertrochanteric line, an objective and valid technique to measure the amount of malrotation in this area seems necessary for clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, any malrotation of the femur comes with impairment in patient outcomes, regardless of location, when considering osteosynthesis. While issues with malrotation in the femoral shaft are described [11,12,17,[21][22][23][24][25], Male ´ř et al report a doubling of cutout rate when malrotation exceeds 15˚in the intertrochanteric region, showing the need for anatomic reduction [26]. Fractures of the basicervical femoral neck are treated with osteosynthesis.…”
Section: Discussionmentioning
confidence: 99%